INTERACTIVE METHODS BASED ON INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN PRIMARY EDUCATION - Khoshbok NORBOTAEV; Dilshod KHUDOYSHUKUROV (Scholar Express Journal, 2022)
In the article, the active use of innovative pedagogical technologies in the educational process, increasing the effectiveness of education, analysis and implementation, the current stage of development of the world education system, the experience of using modern pedagogical technologies, national and historical, ideological conditions - to respond to the conditions, to develop the mindset, consciousness, worldviews of elementary school students, to transform them from free listeners to free participants, to adapt lessons organized on the basis of innovative pedagogical technologies to the needs of students, as well as to students' learning motivation to achieve the goal based on arousing the interest, desire and desire to master the materials, and the effectiveness of the use of methods based on innovative pedagogical technologies is highlighted
Keywords: Innovation; primary class; technology; interactive